CODE SWITCHING IN ESP CLASSROOM CONVERSATION: A FOCUS ON LECTURER-STUDENTS INTERACTION AT THE UNIVERSITY LEVEL - Inni Ayati; Tri Widyastuti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2021)
The study was conducted in order to figure out (1) the types of code switching; (2) the functions and the situation of code switching occurrence in the classroom conversation between the lecturer and the students. The data of this descriptive qualitative study were collected through classroom observation towards students majoring in Biology. The result of the study showed (1) almost all types of code switching were used by the lecturer and the students in the conversation with the exception that the lecturer did not have a change of intonation; (2) the switching mostly occurred in whilst teaching session such as discussion and questions and answers session; (3) the students switched their code for fulfilling the functions such as for doing unofficial interaction, expressing emotion, reiterating, and giving command; (4) the functions of the lecturer’s code switching were for clarification, self-correction, calling for attention, and explanation.